2013
DOI: 10.1016/j.dcn.2013.06.005
|View full text |Cite
|
Sign up to set email alerts
|

How age of bilingual exposure can change the neural systems for language in the developing brain: A functional near infrared spectroscopy investigation of syntactic processing in monolingual and bilingual children

Abstract: Is the developing bilingual brain fundamentally similar to the monolingual brain (e.g., neural resources supporting language and cognition)? Or, does early-life bilingual language experience change the brain? If so, how does age of first bilingual exposure impact neural activation for language? We compared how typically-developing bilingual and monolingual children (ages 7-10) and adults recruit brain areas during sentence processing using functional Near Infrared Spectroscopy (fNIRS) brain imaging. Bilingual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
85
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 75 publications
5
85
1
1
Order By: Relevance
“…By virtue of the closer connection with other parts of the brain (e.g., frontal area), the left fusiform activity was likely to be enhanced in early bilinguals during their L1 processing. However, our finding appears to be inconsistent with Jasinska and Petitto's (2013) findings that bilateral prefrontal cortex and bilateral superior temporal gyrus were more activated for late than early bilingual children during sentence judgment task in L1 (Jasinska & Petitto, 2013). Probably, differentiated ages of samples (9 year-old children in their study vs. 20 + year-old adults in this study), differentiated language aspects assessed (sentential in their study vs. articulatory, orthographic, phonological, semantic, and sentential in this study), and differentiated definitions of early bilinguals (before 4 year-old in their study vs. before 7 year-old in this study) are all contributable to the incongruent findings in terms of whether early or late bilinguals need more neural resources for L1 processing (late in their study vs. early in this study) and which specific cortical areas are differentially activated between early and late bilinguals during their L1 processing (B PFC and B STG in their study vs. L FG in this study).…”
Section: The Effect Of L2 Aoa On L1 Networkcontrasting
confidence: 81%
See 1 more Smart Citation
“…By virtue of the closer connection with other parts of the brain (e.g., frontal area), the left fusiform activity was likely to be enhanced in early bilinguals during their L1 processing. However, our finding appears to be inconsistent with Jasinska and Petitto's (2013) findings that bilateral prefrontal cortex and bilateral superior temporal gyrus were more activated for late than early bilingual children during sentence judgment task in L1 (Jasinska & Petitto, 2013). Probably, differentiated ages of samples (9 year-old children in their study vs. 20 + year-old adults in this study), differentiated language aspects assessed (sentential in their study vs. articulatory, orthographic, phonological, semantic, and sentential in this study), and differentiated definitions of early bilinguals (before 4 year-old in their study vs. before 7 year-old in this study) are all contributable to the incongruent findings in terms of whether early or late bilinguals need more neural resources for L1 processing (late in their study vs. early in this study) and which specific cortical areas are differentially activated between early and late bilinguals during their L1 processing (B PFC and B STG in their study vs. L FG in this study).…”
Section: The Effect Of L2 Aoa On L1 Networkcontrasting
confidence: 81%
“…However, this behavioral finding has not been ascertained by neuroimaging data. The only related published neuroimaging study found that, compared to early bilingual children, L1 sentence processing in late bilingual children was associated with greater activation in the bilateral prefrontal cortex and the bilateral superior temporal gyrus (Jasinska & Petitto, 2013). This implies that L2-to-L1 influence is greater for later bilinguals; which is opposite to the behavioral finding that early bilinguals are subject to greater influence from L2 to L1 (Gathercole & Moawad, 2010;Pavlenko, 2011).…”
Section: Introductionmentioning
confidence: 88%
“…Research on second language learning outcomes (Flege, MacKay, & Meador, ; Johnson & Newport, ; Mackay & Flege, ) and language in international adoptees (Jacobs, Miller, & Tirella, ; Mcacham, ) show that exposure to a second language during the first 5 years of life produces the best possible outcomes for full acquisition of the second language. These findings are supported by brain research showing that the processing of early acquired second languages is more efficient compared to later acquired second languages (Jasinska & Petitto, ; Wartenburger et al, ; Weber‐Fox & Neville, , ). Using voxel‐based morphometry (VBM), Mechelli et al () have shown that exposure to two languages before the age of 5 years results in the highest levels of brain tissue density in areas related to language, memory, and attention.…”
Section: Age Of Acquisitionmentioning
confidence: 54%
“…tested bilingual and monolingual children using the Simon and Stroop tasks and found that bilingual children recruited the bilateral cingulate cortex to a greater extent than monolinguals on conflict trials. Converging findings from two other studies show that bilingual children over‐recruit frontal resources when completing theory‐of‐mind tasks and reading (though the latter is confounded by the linguistic nature of the task). Although the evidence from functional studies with children is limited, this over‐recruitment may be a by‐product of bilingual children attempting to master two languages at this stage of development.…”
Section: Bilingualism As a Model Of Efficiency: The Bilingual Anteriomentioning
confidence: 99%